Harnessing Artificial Intelligence in Education: Building Cultural Literacy and Advancing the Sustainable Development Goals - Maritasari, Donna Boedi; Apriana, Dina; Hudri, Muhammad (Tadris: Jurnal Keguruan dan Ilmu Tarbiyah, 2025)
This study examines teachers’ perceptions of Artificial Intelligence (AI) integration in education, with a particular focus on its impact on cultural literacy and its contributions to the Sustainable Development Goals (SDGs). The study employs a quantitative descriptive design, involving 25 teachers from SD Islam Prihaswari in East Lombok, Indonesia, who were selected through purposive sampling. Data were collected between July and August 2025 using a Likert-scale questionnaire consisting of 20 items distributed across four dimensions: AI utilization, cultural awareness, contribution to SDGs, and readiness and challenges. Data analysis employed descriptive statistics, including mean scores, standard deviations, percentage indices, 95% confidence intervals, and categorical interpretations. The results indicate an overall positive perception of AI integration in education. The highest mean score was observed in the SDGs dimension (M = 4.90, SD = 0.30, CI95% = 4.78–5.02), while the utilization dimension received the lowest score (M = 4.20, SD = 0.65, CI95% = 4.03–4.37). These findings suggest that teachers recognize AI’s potential to strengthen cultural literacy and support sustainable education, although practical implementation remains constrained by infrastructural and pedagogical limitations. The study highlights the need for improved digital infrastructure, systematic teacher training, and culturally responsive AI-based learning models to ensure meaningful and sustainable integration of AI in education